Towards interactive learning style in accounting: the game approach / Wan Mardyatul Miza Wan Tahir...[et.al] - Wan Tahir, Wan Mardyatul Miza; Mohd Noor, Ida Haryanti; Daud, Dalila; Hussin, Amariah Hanum (Universiti Teknologi MARA, Cawangan Melaka, 2018)
Students nowadays often inattentive with typical lecture-based approaches to introductory accounting courses. The VARK (Visual, Aural, Read/Write and Kinesthetic) model learning style adopted in developing a game to attract students’ interest to the subject. The game consist of more than 50 colorful cards inspired by real life business transactions within the context in accounting textbooks on a fundamental level. These approaches allow students to engage in experiential and social learning while capture different preference of students’ learning style. The result showed that the game approach was both more effective in improving students’ knowledge of accounting principle, encourage competitiveness, teamwork, decision making ability and more motivational than the traditional approach.